Anti-Diabetic Effect of a Flavonoid and Sitosterol - Rich Aqueous Extract of Pleurotus tuberregium Sclerotia in Alloxan-Induced Diabetic Rabbits - Onuekwuzu, Ifeanacho M.; Chidinma, Ikewuchi Catherine; Chigozie, Ikewuchi Jude (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Objective: Traditionally prepared infusions and decoctions are commonly used in the management of diabetes mellitus, in southern Nigeria; one of such is the aqueous extract of the sclerotia of Pleurotus tuberregium (“usu” milk). In this study, the effects of the extract on the body weights, tissue/ organ weights, fasting blood glucose, blood/plasma lipid profiles and atherogenic indices were investigated in normal and alloxan-induced diabetic rabbits. Methods: Diabetes mellitus was induced by the injection of alloxan (120 mg/kg body weight) via the marginal ear vein. The extract was administered orally at 100, 200 and 300 mg/kg to normal and diabetic rabbits; while metformin was administered at 50 mg/kg. The crude extract was analyzed by gas chromatography, coupled to flame ionization detector. Results: Thirty-one known flavonoids were detected, consisting mainly of isoquercetin (28.5%), luteolin (24.3%), quercetin (18.8%) and kaempferol (11.3%). Sitosterol (82.0%) and stigmasterol (12.5%) were the most abundant of the seven phytosterols detected. Compared to the diabetic control, the treatment significantly (p<0.05) lowered the weights of the kidney and liver, as well as the levels of blood glucose and triglyceride, plasma VLDL, LDL and non-HDL cholesterol, atherogenic index of plasma, cardiac risk ratio, atherogenic coefficient and Castelli’s risk index II. It, however, significantly (p<0.05) increased plasma HDL cholesterol, without significantly affecting blood total cholesterol levels. Conclusion: This study showed that the extract was hypoglycemic, and improved lipid profile and atherogenic indices, thus highlighting its cardioprotective potential, thereby supporting its use in the management of diabetes mellitus.
Keywords: phytosterols